Challenges in IPF diagnosis, current management and future perspectives: Patient case 2 - Margaritopoulos, George (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Patient presentation and diagnosisThe patient is a 73-year-old male retired house painter and ex-smoker who was admitted to the respiratory medicine department of a district hospital in Greece due to the presence of streaks of blood in his sputum. His past medical history included coronary artery disease, arterial hypertension and supraventricular tachycardia (SVT). A high resolution computed tomography (HRCT) was performed which showed enlarged mediastinal lymph nodes with evidence of fibrosis.[...]